Menilik Realitas Kebutuhan Pengguna Lulusan Teknologi Pendidikan Pada Bidang Jasa E-Learning di Indonesia - Briliana Firdaus; Shafira Aulia Darmawan; Raffie Ahmad Riesman Putra; Laksmi Dewi (Educatio, 2022)
The Covid-19 pandemic has transformed conventional learning towards the use of e-Learning. Educational technology is a field of study that labels graduates with the main profile as developers of learning technology, one of which has competence in the sector of e-Learning. As a result, this study aims to look at the realities of the demands of educational technology graduates in the field of e-Learning services in Indonesia, both in terms of relevant institutions and based on the alumni job experience. The author conducts descriptive research using qualitative methods, including interviews with two samples of e-Learning service institutions in Indonesia (PT Menara Indonesia and PT Zeniora Edukasi Teknologi), as well as the distribution of open qualitative questionnaires to three alumni of Universitas Pendidikan Indonesia who are currently working in e-Learning service institutions. Work documents that support the research are also used to conduct documentation studies. The data was analyzed using various methods, including reduction and organization, as well as triangulation and re-checking with investigators. Based on the study's findings, it can be concluded that educational technology graduates are needed in e-Learning service institutions, both to receive graduates who fulfill the institution's criteria and the linearity of positions gained by educational technology alumni.